2018
DOI: 10.15632/jtam-pl.56.3.645
|View full text |Cite
|
Sign up to set email alerts
|

TIG and laser beam welded joints – simplified numerical analyses

Abstract: Regardless of the welding method, a new joint and the surrounding area are inevitably subjected to thermo-physical perturbation. The paper presents analyses of many different issues involved in welding and potential solutions including adoption of simplifying assumptions, application of numerical algorithms and development of reliable representative models. The Finite Element Method is used to determine residual stress distribution, using results from thermo-physical tests and widely known mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Modification of the surface layer of machine components can have a significant effect on improving their mechanical properties [1][2][3][4][5][6][7]. One important factor in the initiation and development of fatigue cracks concerns structural and geometric notches, which cause local accumulation of stresses favoring the weakening of the structure [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of the surface layer of machine components can have a significant effect on improving their mechanical properties [1][2][3][4][5][6][7]. One important factor in the initiation and development of fatigue cracks concerns structural and geometric notches, which cause local accumulation of stresses favoring the weakening of the structure [7].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the surface crushing created by surface peening leads to compressive stresses in the subsurface layers affecting crack development. In non-surface-strengthened specimens, crack initiation usually occurs at the bottom of structural or geometric notches, whereas the introduction of a state of subsurface compressive stresses can shift the crack initiation site to the point of maximum material stress below the surface [5,15] and, most importantly, increase fatigue life.…”
Section: Introductionmentioning
confidence: 99%